2001
DOI: 10.1007/s100960100629
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Serological Tests and Blood Culture to the Early Diagnosis of Systemic Candidiasis

Abstract: The isolation of Candida species from a single blood culture is considered sufficient evidence for the initiation of systemic antifungal therapy. However, blood cultures still lack sensitivity. Previous reports have suggested that the combined serological detection of mannanemia and anti-mannan antibodies may be useful for the diagnosis of systemic candidiasis caused by Candida albicans (specificity and sensitivity 93% and 80%, respectively). In this study, serological tests to detect Candida albicans mannan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 30 publications
4
66
0
6
Order By: Relevance
“…An advantage in early diagnosis using Mn/A-Mn detection was reported in five studies, both in hematological and ICU patients. 46,48,52,53,55 Mn-and A-Mn-positive results preceded blood cultures in 73% of 45 patients with candidemia by a mean of 6 and 7 days, respectively. 55 In 21 patients with hepatosplenic IC, 18 (86%) were Mn-and/or A-Mnpositive at a median of 16 days before radiological detection of liver or spleen lesions.…”
Section: Mannan Ag (Mn)/anti-mannan Ab (A-mn)mentioning
confidence: 92%
See 2 more Smart Citations
“…An advantage in early diagnosis using Mn/A-Mn detection was reported in five studies, both in hematological and ICU patients. 46,48,52,53,55 Mn-and A-Mn-positive results preceded blood cultures in 73% of 45 patients with candidemia by a mean of 6 and 7 days, respectively. 55 In 21 patients with hepatosplenic IC, 18 (86%) were Mn-and/or A-Mnpositive at a median of 16 days before radiological detection of liver or spleen lesions.…”
Section: Mannan Ag (Mn)/anti-mannan Ab (A-mn)mentioning
confidence: 92%
“…46,48,52,53,55 Mn-and A-Mn-positive results preceded blood cultures in 73% of 45 patients with candidemia by a mean of 6 and 7 days, respectively. 55 In 21 patients with hepatosplenic IC, 18 (86%) were Mn-and/or A-Mnpositive at a median of 16 days before radiological detection of liver or spleen lesions. 48 Based on the literature review, Mn and A-Mn offer a diagnostic aid in patients with suspected IC.…”
Section: Mannan Ag (Mn)/anti-mannan Ab (A-mn)mentioning
confidence: 92%
See 1 more Smart Citation
“…There has been less enthusiasm for antibody detection as a diagnostic strategy because of concerns regarding false-negative tests in immunocompromised patients (26). Nevertheless, recent studies detecting antibodies against SAP (19,20), ENO1 (13,16), mannan (30,33,36), a 52-kDa metalloprotein (6), hyphal wall protein 1 (HWP1) (14), and a Candida albicans germ tube antigen (CGTA) (26) reported sensitivities and specificities that are consistent with those of other diagnostic markers, even among highly immunocompromised hosts like stem cell transplant and liver transplant recipients (11,12,21,31,34). Moreover, various combinations of an antibody test with an antigen test have been shown to be superior to either test alone in diagnosing systemic candidiasis (23,28,29).…”
mentioning
confidence: 99%
“…For all of them, sensitivity is impaired by the rapid clearance by host catabolism of epitopes from the bloodstream (14, 21, 33). We have developed an enzyme immunoassay (EIA) for the detection of mannan and shown that its combination with detection of antimannan antibodies was useful for the early diagnosis of systemic candidiasis (32,33,44); these tests have been recently marketed as the Platelia Candida Ag and Platelia Candida Ab tests, respectively. The Platelia Candida Ag test detects an ␣-linked oligomannose residue (␣-Man) epitope whose circulation was transient.…”
mentioning
confidence: 99%